2020
DOI: 10.1097/ana.0000000000000594
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlactatemia After Intracranial Tumor Surgery Does Not Affect 6-Month Survival: A Retrospective Case Series

Abstract: Background: Patients undergoing neurosurgery frequently exhibit hyperlactatemia. The aim of this study was to identify factors associated with hyperlactatemia and assess how hyperlactatemia impacts survival and hospital length of stay after intracranial tumor surgery. Materials and Methods: This retrospective cohort study included 496 adult patients that underwent surgery between January 1, 2014 and December 31, 2015. We evaluated patient characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 33 publications
0
32
0
1
Order By: Relevance
“…e research was conducted up to April 2019 and yielded 215 studies. e articles [1][2][3]5,9,14] in which the correlation between the level of serum lactate and intracranial tumors was studied are reported in Table 4. In an initial series of 18 patients submitted to craniotomy for intracranial tumor, the authors found an increase of serum lactate during surgery regardless to the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e research was conducted up to April 2019 and yielded 215 studies. e articles [1][2][3]5,9,14] in which the correlation between the level of serum lactate and intracranial tumors was studied are reported in Table 4. In an initial series of 18 patients submitted to craniotomy for intracranial tumor, the authors found an increase of serum lactate during surgery regardless to the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…is is an important topic to address in future although the previous studies failed to demonstrate a correlation between increased serum lactate and patient's prognosis. [2,3,14]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,24 In a few studies, similar to our results, the effect of persistent high lactate levels on survival has not been demonstrated. 6,25 One of the strengths of the study is that the research included repetitive measurements in lactate measurement instead of just a single blood sample. The lactate values measured before completion of the surgery were supported by four following measures in the early postoperative period, and the relationship between different variables and persistent elevations was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, an overlap frequently occurs between the two types [1,7,8]. A high prevalence of hyperlactatemia has been shown during and after craniotomy for brain tumor resection among adults [9][10][11]. The clinical significance of hyperlactatemia in this setting is unclear.…”
Section: Introductionmentioning
confidence: 99%